THE EFFECT OF ITRAINING ON EMPLOYEE PERFORMANCE AT THE BINA MARGA CIPTA KARYA TATA RUANG PERTAHANAN DAN PERUMAHA RAKYAT KABUPATEN SIDENRENG RAPPANG - Fadly, Muhammad; Haeril, Haeril; Taufiq, Muhammad (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine whether there is an effect between training on employee performance at the Department of Public Works, Public Works, Spatial Planning, Land and Public Housing of Sidenreng Rappang Regency. The population in this study were all employees at the Department of Public Works, Public Works, Spatial Planning, Land and Public Housing of Sidenreng Rappang Regency, totaling 39 people, and the sampling technique used was saturated sampling. Data were obtained from primary data and secondary data, data collection techniques used were observation, questionnaires and documentation, the method used in this study was a quantitative research method. The results of the analysis show that training has a significant influence on employee perfomance, with a calculted t value (3,154) which is greater than the t tabel (1,687). Therefore, the hypothesis which states that there is an influence of training on employee perfomance can be accepted. The coeffcient of determination (R square) value is 43,8%, indicating that 43,8% of employee performance variability can be explaining 56,2% is influenced by other factors outside the variabel studied.